The Mannose Receptor Is Involved in the Phagocytosis of Mycobacteria-Induced Apoptotic Cells - Teresa Garcia-Aguilar; Patricia Espinosa-Cueto; Alejandro Magallanes-Puebla; Raúl Mancilla (Journal of Immunology Research)
Upon Mycobacterium tuberculosis infection, macrophages may undergo apoptosis, which has been considered an innate immune response. The pathways underlying the removal of dead cells in homeostatic apoptosis have been extensively studied, but little is known regarding how cells that undergo apoptotic death during mycobacterial infection are removed. This study shows that macrophages induced to undergo apoptosis with mycobacteria cell wall proteins are engulfed by J-774A.1 monocytic cells through the mannose receptor. This demonstration was achieved through assays in which phagocytosis was inhibited with a blocking anti-mannose receptor antibody and with mannose receptor competitor sugars. Moreover, elimination of the mannose receptor by a specific siRNA significantly diminished the expression of the mannose receptor and the phagocytosis of apoptotic cells. As shown by immunofluorescence, engulfed apoptotic bodies are initially located in Rab5-positive phagosomes, which mature to express the phagolysosome marker LAMP1. The phagocytosis of dead cells triggered an anti-inflammatory response with the production of TGF-β and IL-10 but not of the proinflammatory cytokines IL-12 and TNF-α. This study documents the previously unreported participation of the mannose receptor in the removal of apoptotic cells in the setting of tuberculosis (TB) infection. The results challenge the idea that apoptotic cell phagocytosis in TB has an immunogenic effect.